Chitosan-Calcium-Simvastatin Scaffold as an Inductive Cell-Free Platform. (September 2021) - Soares, D.G.; Bordini, E.A.F.; Bronze-Uhle, E.S.; Cassiano, F.B.; Silva, I.S.P.; Gallinari, M.O.; Matheus, H.R.; Almeida, J.M.; Cintra, L.T.A.; Hebling, J.; de Souza Costa, C.A.
The development of biomaterials based on the combination of biopolymers with bioactive compounds to develop delivery systems capable of modulating dentin regeneration mediated by resident cells is the goal of current biology-based strategies for regenerative dentistry. In this article, the bioactive potential of a simvastatin (SV)–releasing chitosan-calcium-hydroxide (CH-Ca) scaffold was assessed. After the incorporation of SV into CH-Ca, characterization of the scaffold was performed. Dental pulp cells (DPCs) were seeded onto scaffolds for the assessment of cytocompatibility, and odontoblastic differentiation was evaluated in a microenvironment surrounded by dentin. Thereafter, the cell-free scaffold was adapted to dentin discs positioned in artificial pulp chambers in direct contact with a 3-dimensional (3D) culture of DPCs, and the system was sealed to simulate internal pressure at 20 cm/H2 O. In vivo experiments with cell-free scaffolds were performed in rats' calvaria defects. Fourier-transform infrared spectroscopy spectra proved incorporation of Ca and SV into the scaffold structure. Ca and SV were released upon immersion in a neutral environment. Viable DPCs were able to spread and proliferate on the scaffold over 14 d. Odontoblastic differentiation occurred in the DPC/scaffold constructs in contact with dentin, in which SV supplementation promoted odontoblastic marker overexpression and enhanced mineralized matrix deposition. The chemoattractant potential of the CH-Ca scaffold was improved by SV, with numerous viable and dentin sialoprotein–positive cells from the 3D culture being observed on its surface. Cells at 3D culture featured increased gene expression of odontoblastic markers in contact with the SV-enriched CH-Ca scaffold. CH-Ca-SV led to intense mineralization in vivo, presenting mineralization foci inside its structure. In conclusion, the CH-Ca-SV scaffold induces differentiation of DPCs into a highly mineralizing phenotype in the presence of dentin, creating a microenvironment capable of attracting pulp cells to its surface and inducing the overexpression of odontoblastic markers in a cell-homing strategy.